3(4x-3)+1=(3x-1)-2(x-2)

Simple and best practice solution for 3(4x-3)+1=(3x-1)-2(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x-3)+1=(3x-1)-2(x-2) equation:


3(4x-3)+1=(3x-1)-2(x-2)

We simplify the equation to the form, which is simple to understand
3(4x-3)+1=(3x-1)-2(x-2)

Reorder the terms in parentheses
+(+12x-9)+1=(3x-1)-2*(x-2)

Remove unnecessary parentheses
+12x-9+1=+(+3x-1+)-2+*(+x-2+)

Remove unnecessary parentheses
+12x-9+1=3x-1-2*(x-2)

Reorder the terms in parentheses
+12x-9+1=3x-1+(-2x+4)

Remove unnecessary parentheses
+12x-9+1=+3x-1-2x+4

We move all terms containing x to the left and all other terms to the right.
+12x-3x+2x=-1+4+9-1

We simplify left and right side of the equation.
+11x=+11

We divide both sides of the equation by 11 to get x.
x=1

See similar equations:

| (-x)-46=3-6x | | 12a-13=3 | | 2x^3-11x^2+5x=0 | | .30x+.05(10-x)=.10(20) | | 3(2x-2)=-4(x+4) | | 2x^3+5x^2-14x-8=0 | | 2x^2-120=0 | | -3h+21-3=-2-3h+12+13h | | (4u+3)(8-u)=0 | | 7x-2x(x-3)=5x+2 | | 3m-5n=8r | | 5h+7-2h-3=-2 | | x+11=3x+3 | | 3.04=x+1.52x | | 3(x+9)=12 | | x=3p+n | | 16x^2+64x+60=0 | | 5xa=120 | | 14x-29=-13 | | 16x^2+64+60=0 | | 0.2x-8=-2-z | | 5x-11=3x+4 | | 2x^2+21x=-54 | | 8j+4-3h=1+4h-2 | | 3x+2(x-2)=4x-23+2x | | 14c+7-8c=37 | | 9x^2+33x-60=0 | | 4(13)+141.2= | | 2y+3x=-16 | | 1(3x-4)=5(x-6)+1 | | -2g=-8 | | 5-2y=2(y+3) |

Equations solver categories